PROBABILITY THEORY ISSUES MATHEMATICAL MODEL CONCLUSION - Abdimumin Abdiraxmanov; To'raeva Farangiz (Journals Park Publishing, 2024)
Its effects or the result of a random experiment is any fundamental physics of a phenomenon called. Experience consists of all the fundamental forces of physics phenomena that can happen as a result of the package of the fundamental forces of physics phenomena space or the package space, and we are called through the understanding of the character, while each is a phenomenon of physics fundamental understanding of the character through
Keywords: Its effects or the result of a random experiment is any fundamental physics of a phenomenon called. Experience consists of all the fundamental forces of physics phenomena that can happen as a result of the package of the fundamental forces of physics phenomena space or the package space, and we are called through the understanding of the character, while each is a phenomenon of physics fundamental understanding of the character through